Efektivitas Konseling Kelompok Cognitive Behavior Therapy untuk Mengurangi Kecemasan Santri pada Kegiatan Muhadhoroh di Pesantren - Syarifah Syarifah; Nur Hermatasiyah; Putri Nurina (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This study aimed to examine the effectiveness of Cognitive Behavior Therapy (CBT)-based group counseling in reducing students' anxiety during muhadhoroh (public speaking) activities at an Islamic boarding school. A quantitative approach with a quasi-experimental pretest-posttest control group design was employed. The participants consisted of 20 seventh-grade female students selected through purposive sampling from 45 students who exhibited moderate to high levels of public speaking anxiety.They were divided into an experimental group and a control group, each consisting of 10 participants. The experimental group received five sessions of CBT-based group counseling, whereas the control group received no intervention. Data were collected using an anxiety questionnaire and analyzed through Shapiro-Wilk normality test, Levene's homogeneity test, paired sample t-test, independent sample t-test, and N-Gain analysis. The findings indicated that the data were normally distributed and homogeneous. The experimental group showed a significant reduction in anxiety scores from a mean of 82.70 to 53.60, while the control group showed only a slight decrease from 76.80 to 73.70. The independent sample t-test revealed a significant difference between groups (p < 0.001), supported by a very large effect size (Cohen's d = -2.664). Furthermore, the experimental group achieved an N-Gain score of 0.526 (52.64%), categorized as effective, whereas the control group obtained only 0.063 (6.33%). These findings demonstrate that CBT-based group counseling is effective in reducing students' anxiety during muhadhoroh activities.